2015
DOI: 10.1111/roie.12168
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness and Cross‐country Income Differences

Abstract: Development accounting literature usually attributes the observed cross-country variation in per capita income to dierences in countries' factor endowments and total factor productivity (the Solow residual). While the former can be relatively straightforward interpreted and measured, the latter remains at least partly a black box. In this paper, we provide a structural interpretation for dierences in total factor productivity across countries and quantitatively explore the role of trade barriers in explaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…They found that trade, remittances, interest rate and urbanization increases income inequality, while FDI reduces inequality. Hepenstrick and Tarasov (2015) investigated how variations in trade openness contribute to cross-country income differences. The study calibrated the model for the year 2003 for 86 countries by using OLS and the Poisson pseudo maximum likelihood.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that trade, remittances, interest rate and urbanization increases income inequality, while FDI reduces inequality. Hepenstrick and Tarasov (2015) investigated how variations in trade openness contribute to cross-country income differences. The study calibrated the model for the year 2003 for 86 countries by using OLS and the Poisson pseudo maximum likelihood.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on globalization (as international trade) and income inequality is divided into two strands. The first strand advocated that due to increase in trade globalization there is an increase in income inequality (Rudra, 2004; Silva and Leichenko, 2004; Felbermayr, 2005; Beckfield, 2006; Ali and Isse, 2007; Meschi and Vivarelli, 2009; Bensidoun et al , 2011; Lu and Cai, 2011; Cassette et al , 2012; Demir et al , 2012; Rodriguez-Pose, 2012; Munir et al , 2013; Hepenstrick and Tarasov, 2015, Munir and Sultan, 2017). The second strand argued that due to increase in trade globalization, there is a decrease in income inequality (Chakrabarti, 2000; Silva, 2007; Babones and Zhang, 2008; Tian et al , 2008; Georgantopoulos and Tsamis, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Rodríguez-Pose (2012) researched that rising economic globalization has a beneficial effect on global disparities, and trade contracts had a more substantial influence on income disparity in middle and low-income economies than high-income countries. Hepenstrick and Tarasov (2015) explored how fluctuations in trade openness lead to income gaps across the world. The study found that there would be no disparity owing to trade openness if the states were utterly symmetric.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The causative impacts of globalization on income inequality are a major issue of academic concern. Ali and Isse (2007); Aradhyula, Rahman, and Seenivasan (2007); Beckfield (2006); Bensidoun, Jean, and Sztulman (2011); Cassette, Fleury, and Petit (2012); Demir, Ju, and Zhou (2012); Felbermayr (2005); Hepenstrick and Tarasov (2015); Kai and Hamori (2009;Lu and Cai (2011); Meschi and Vivarelli (2009); Munira, Kianib, Khanc, and Jamald (2012); Rodríguez-Pose (2012); Rudra (2004); Silva & Leichenko, 2004;Wagle (2007) , etc. claim that globalization is rising income inequality in various regions at different periods. Stiglitz (2002) argued that globalization has negative consequences on, especially weak economies.…”
Section: Introductionmentioning
confidence: 99%
“…Major portion of the literature identified that higher trade openness increases inequality in the country for example but not limited to (Revenga, 1997;Milner and Wright, 1998;Levinsohn, 1999;Ravallion, 2001;Epifani, 2003;Lundberg and Squire, 2003;Melitz, 2003;Xu, 2003;Khondker and Raihan, 2004;Annabi et al, 2005;Milanovic, 2005;Yeaple, 2005;Bustos, 2007;Conte and Vivarelli, 2007;Meschi and Vivarelli, 2009;Barua and Chakraborty, 2010;Bergh and Nilsson, 2010;Li and Coxhead, 2011;Ezcurra and Rodriguezpose, 2013;Furusawa and Konishi, 2013;Grossman and Helpman, 2014).On the other hand, some studies concluded that trade reduces income inequality (Bourguignon and Morrisson, 1990;Wood, 1995;Calderón and Chong, 2001;Cornia and Kiiski, 2001;Ravallion, 2001;Lundberg and Squire, 2003;Wade, 2004;Milanovic and Squire, 2005;Easterly, 2006;Demir et al, 2012) and some studies found mixed results (Meschi and Vivarelli, 2009;Nissanke and Thorbecke, 2010;Castilho et al, 2012;Perera et al, 2014;Hepenstrick and Tarasov, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%